2010
DOI: 10.3382/ps.2009-00570
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology, immunohistochemistry, in situ apoptosis, and ultrastructure characterization of the digestive and lymphoid organs of new type gosling viral enteritis virus experimentally infected gosling

Abstract: Here, for the first time, to colocalize new type gosling viral enteritis virus (NGVEV) with histological lesions and in situ apoptosis in the digestive organs (esophagus, proventriculus, gizzard, small intestine, cecum, rectum, liver, and pancreas) and the lymphoid organs (bursa of Fabricius, thymus, Harderian gland, and spleen) of experimentally infected goslings, portions of tissues were collected at sequential infection time points and examined by histopathology for histological lesions, immunohistochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Beta cells are responsible for the secretion and storage of insulin in response to decreased plasma glucose concentrations. Insulin regulates carbohydrate metabolism and has anti-apoptotic effects on pancreatic cells [21] . In common mammalian species, the beta cells are located in the center of the endocrine islets [1,11] .…”
Section: Insulinmentioning
confidence: 99%
“…Beta cells are responsible for the secretion and storage of insulin in response to decreased plasma glucose concentrations. Insulin regulates carbohydrate metabolism and has anti-apoptotic effects on pancreatic cells [21] . In common mammalian species, the beta cells are located in the center of the endocrine islets [1,11] .…”
Section: Insulinmentioning
confidence: 99%
“…After acute (5 d PI) or chronic (19 d PI) virus infection, the transcription levels of goose TLR7 were greater during chronic infection than during acute infection in the thymus, bursa of Fabricius, spleen, or small intestine. Interestingly, our previous studies suggested that NGVE virus is widely distributed in lymphoid organs, such as the small intestine and bursa of Fabricius [43]. Moreover, goslings infected with NGVEV will develop digestive symptoms and show impaired immune function [44].…”
Section: Discussionmentioning
confidence: 98%
“…The intestinal permeability of the former mice increased, while the bacterial mix in the intestinal microbiome of the latter mice changed and reduced the diversity of fecal bacteria, suggesting that the interaction between the immune system and Lactobacillus may be conservative [69,70]. In addition, there are reports that the significantly increased abundance of Lactobacillus in small bowel transplant, surgical patients, chronic spontaneous urticaria patients, and diabetic patients was also observed [71][72][73][74]. Other studies have found that high-calorie diet causes significant concentrations of 16…”
Section: Discussionmentioning
confidence: 99%